Cardiac voltage-sodium channel mutations association with primary electrical diseases - El-Battrawy, Ibrahim; Lang, Siegfried; Zhou, Xiao-Bo; Borggrefe, Martin; Akın, Ibrahim (Europace, 2018)
The article by Moreau et al.1 published in Europace describing the association between voltage-gated sodium channel mutations and the occurrence of stroke in yo
Gesehen am 02.10.2019